Helena Star : an epic adventure through the murky underworld of international drug smuggling - Riley, Stewart (Robert Reed Publishers, 2021)
"On April 17, 1978, the U.S. Coast Guard seized the aging freighter off Washington State's coast with is hold loaded with 37 tons of marijuana- the west coast's largest pot bust- worth an estimated street value of $74 million. Drug agents later seized the sleek Joli, a 61-foot sailboat, for its suspected role in the case. A past winner of the prestigious Victoria to Maui sailboat race, the Joli had been purchased from William Niemi, Jr., former president of Eddie Bauer, by champion freestyle skier Mike Lund. Author Stewart Riley, the attorney for the captain of the Helena Star, provides an insider's unvarnished account of the case from the trenches. The freighter and the conspirators involved were in the news from its seizure in 1978 to its death by sinking in 2013. This drug bust and the ensuing events comprise a true saga about the inner workings of a Colombian-American drug cartel, smuggling on a massive scale, money laundering, the capture of fugitives in Bolivia, suspicious deaths, the lives of high-profile individuals, and courtroom battles in Seattle and San Francisco."-- back cover